Diversidade de mirmecofauna (Hymenoptera, formicidae) e sua potencialidade para o monitoramento de áreas guiadas pela agricultura sintrópica - Benedetti, João Fernando de Almeida (2017)
Sintropic Agriculture (AS) contributes to the improvement of ecosystem services: it increases biodiversity, promotes nutrient cycling and promotes high interaction capacity. This is pointed from a dominance of forest environment as productive strategy. Ernst Götsch considers ants as our "teachers", always present in the productive area. From this point of view, they are considered great bioindicators to monitor AS. The collected was made with help of pitfall trap in two rural properties: 1. Fazenda São Luiz / SP and 2. Fazenda Olhos d'Água / BA. Each one with three sampling areas: I. MT- Forest Fragment, SAFI - older agroforestry system and SAFII - more recent. Seventy-one species / morpho-species were collected in six subfamilies and 29 genera. The sintropic practice to handle the SAFs favors the trophic chain, community structure, composition and complexifies the systems creating niches for the ants. It is necessary to expand the diversification of studied niches. The collection was distributed in 13 guilds and managed to point out some alternatives for the elaboration of a participatory monitoring protocol. Suggested the guilds are: great predators, camponotíneas patrolmen, desfolheadoras (leaf mower), myrmecíneas generalists, small specialists, pseudo mirmecíneos patrolmens, small opportunists, crípticas de serrapilheira (leaf litter) poneríneas, and crípticas de serrapilheira (leaf litter) myrmecíneo.